2017
DOI: 10.15171/ijb.1558
|View full text |Cite
|
Sign up to set email alerts
|

Designing Two Individual AcMNPV Polyhedrin-Plus Bac-to-Bac Expression System in order to Express GFP and CPV-VP2 in Insect Cells

Abstract: Background:The importance of viral protein-2 (VP2) of canine parvovirus (CPV) in binding to human cancer cells, production of veterinary vaccines and diagnostic kits has motivated several researches on producing this protein. Objectives: Our purpose was to construct recombinant bacmid shuttle vectors expressing VP2 of CPV using Bac-to-Bac baculoviral expression system. Materials and Methods: Mini-Tn7 transposones engineered in pFastBac1 donor vectors were used to construct expression cassettes of GFP and CPV-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…As demonstrated in the previous studies [ 12 – 15 ], first we generated two baculoviruses expressing VP2 and EGFP proteins. The expression of recombinant EGFP protein in the cells infected with recombinant baculoviruses encoding the EGFP gene was observed by an inverted fluorescent microscope.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in the previous studies [ 12 – 15 ], first we generated two baculoviruses expressing VP2 and EGFP proteins. The expression of recombinant EGFP protein in the cells infected with recombinant baculoviruses encoding the EGFP gene was observed by an inverted fluorescent microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The EGFP gene was coupled with the VP2 gene in all steps parallelly, as a control [ 13 , 14 ]. The constructed recombinant bacmids including VP2 and EGFP genes were analyzed by PCR panel, using designed primers and PUC/M13 universal primers and then transfected into Sf9 insect cells using cationic lipids to generate two new recombinant baculoviruses expressing EGFP and CPV-VP2 (Ethic NO.IR.BMSU.REC.1400.037) [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The baculovirus expression system is widely used in protein expression, especially for the expression of large molecular weight proteins and their complexes, such as CSP (148.5 kDa) [18]. The traditional baculovirus expression system often relies on the transfection of recombinant baculovirus DNA isolated from bacteria [31, 32]. In contrast, the Ac-MultiBac system used in this study does not need transfection but employs DAP-deficient bacteria that infect insect cells to produce recombinant baculovirus () [13, 20, 23–25, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that VP2 protein could be produced in E. coli and insect expression system [15,16,[18][19][20][21]. Although E. coli expression system has been used widely for recombinant proteins production in laboratory and industrial scale due to its simplicity and economy, the solubility of target proteins could sometimes be low [22][23][24].…”
Section: Discussionmentioning
confidence: 99%